Hyperthyroidism in childhood: peculiarities of the different clinical pictures - Zirilli, Giuseppina; Velletri, Maria Rosa; Porcaro, Federica; Di Giovine, Giuseppina; Maisano, Pina; La Monica, Giuseppina (Acta Biomedica Atenei Parmensis, 2015)
Background: clinical and biochemical picture of hyperthyroidism in children may significantly change according to its etiologies.Objectives: to report the most recent views about epidemiology, pathophysiology, clinical and biochemical course, diagnostic procedures and management of hyperthyroid syndrome in childhood, according to its different etiologies.Design: Graves’ disease and Hashimoto’s thyroiditis are responsible for 84% and 12%, respectively, of all the cases of hyperthyroidism in childhood. Hyperfunctioning thyroid nodules (